ANALISIS AKAR MASALAH KEMISKINAN MASYARAKAT PESISIR DENGAN PENDEKATAN SISTEM SOSIAL EKOLOGI - Fitrina Nazar; Rahman Rahman; Medi Nopiana; Muhammad Rifqi (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This research was conducted to analyze the root causes of poverty with a socio-ecological system approach. The analytical method used the Socio-Ecological System analysis based on the Burkhard Model and Spidergram Approach. The analysis results showed that aquaculture activities in ponds had a high relationship with ecological integrity. Aquaculture activities were carried out by converting mangroves so that they put pressure on the ecological system. The pressure on ecological systems impacted social systems due to the magnitude of connectivity. Besides, the pressure on the social system was indicated by a decrease in daily income for farmers due to reduced catch from wild shrimp, as well as a decrease in catch and an increase in fishermen's operational costs due to further distance fishing grounds. For the reasons, it was necessary to enforce the rules of spatial use that were parallel with improving the quality of the ecosystem and the coastal environment, as well as fostering recommended technology and community empowerment that was expected to help increase the income of coastal communities. Furthermore, through the provision of adequate educational, health, and religious facilities, thus it could improve the community welfare so that they leave out from poverty problems.